New Techniques for the Detection of Nuclear and Radioactive Agents - Aycik, Gul Asiye (NATO Science for Peace and Security Series B: Physics and Biophysics,, 2009)
Nuclear and radioactive agents are considerable concerns especially after the early 1990s and more attention has been focused on the radiation detection technologies. This book comprises the selected presentations of NATO Advanced Training Course held 26-30 May 2008 in Mugla, Turkey. The contributions represent a wide range of documents related to control, monitoring and measurement methods of nuclear / radioactive isotopes and agents for both fundamental and applied works dealing with their use for different purposes. This book presents environmental data from many locations of different countries and also contains the contributions in the detection/monitoring programs of some authors from CIS countries. The basic goal of this book is to deal with recent developments and applications of environmental monitoring and measurement techniques of environmental radionuclides and nuclear agents as well as the auxiliary techniques. The many recent examples contributed by authors will be useful in monitoring/ measurement studies of radioactive/nuclear agents in the present environment, and can help, not only in carrying out outdoor and laboratory experiments, but also in protection of possible sources of radionuclides and nuclear agents. Especially the contributions of experts and specialists involved in this book assured the highest level of knowledge in the field of techniques for the detection of radioactive and nuclear agents.